2011
DOI: 10.1186/1471-2458-11-281
|View full text |Cite
|
Sign up to set email alerts
|

Parental willingness to pay for child safety seats in Mashad, Iran

Abstract: BackgroundIran has one of the highest rates of road traffic crash death rates throughout the world and road traffic injuries are the leading cause of years of life lost in the country. Using child car safety seats is not mandatory by law in Iran. The purpose of this research was to determine the parental willingness to pay (WTP) for child restraints in Mashad, the second most populated city in Iran with one of the highest rates of road traffic-related deaths.MethodsWe surveyed 590 car-owner parents of kinderga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
5
0
2
Order By: Relevance
“…As highlighted, there was a relationship between income level and purchasing of a new car seat with those in the lower income brackets being less likely to have purchased a new seat from a store or online. This finding is mirrored in other studies where those in lower socio-economic groups were less willing to pay for car seats [45]. The provision of low-cost/subsidised CRS or borrowing schemes would help to mitigate against lower ownership rates.…”
Section: Discussionsupporting
confidence: 54%
“…As highlighted, there was a relationship between income level and purchasing of a new car seat with those in the lower income brackets being less likely to have purchased a new seat from a store or online. This finding is mirrored in other studies where those in lower socio-economic groups were less willing to pay for car seats [45]. The provision of low-cost/subsidised CRS or borrowing schemes would help to mitigate against lower ownership rates.…”
Section: Discussionsupporting
confidence: 54%
“…A national study conducted in Iran and a study in the Fars Province found that the majority of deaths are a result of RTCs involving illiterate victims and the least number of university graduates (81). A study conducted on Iranian families showed that the demand for child care safety seats (CSS) is low in both high and low income countries (82). One study found that a lower economic level was associated with high incidence and mortality of RTCs (83).…”
Section: Resultsmentioning
confidence: 99%
“…This is the stimulus needed to trigger the decision-making process to accept a recommended health action. To reflect the aims of this study (development of guidelines for promotion and publicity), the questions focus on only the external factors; therefore, the questionnaires are based on promotion [14]. For example, from a hospital perspective, "Hospitals should provide child car seats for sale/rent/loan to the mother after giving birth," and from the parents' and surrounding peoples' perspective, "A close friend thinks I should use a CRS when travelling" [15].…”
Section: Health Belief Modelmentioning
confidence: 99%